Bacterial Diversity among the Sediments of Glacial Lakes in the Western Balkans: Exploring the Impact of Human Population. Issue 3 (16th March 2019) - Malešević, Milka; Mirković, Nemanja; Lozo, Jelena; Novović, Katarina; Filipić, Brankica; Kojić, Milan; Jovčić, Branko
Abstract: 16S rRNA gene-based metagenomic approach was used to assess the biodiversity of bacterial communities in the sediments of selected glacial lakes in the Western Balkans and to assess the impact of human population on these microbial communities. Sediment samples were collected from three glacial lakes, viz., Plav Lake (in a zone of the highest impact of human population), Black Lake (a zone of medium impact of human population), and Donje Bare Lake (a remote lake with minimal impact of human population). Canonical correlation analysis analysis indicated correlation between the distance of the lake from urbanized population and bacterial diversity in Donje Bare Lake sediment. Bacterial diversity of Black Lake sediment was correlated with high content of phosphorous and pH value. Chemical compounds exhibiting the most prominent correlation with bacterial diversity of Plav Lake were NH4 -N, K2 O, CaCo3, and total nitrogen . Additionally, CCA analysis indicated that population density was correlated with biodiversity of bacterial communities in Plav Lake sediment, which is the most exposed to human population. Multivariate regression revealed the highest correlation between the presence of Proteobacteria classes and population density and levels of NH4 -N. The influence of human population was observed to be important for shaping the sediment communities in addition to biological and chemical factors.